Kelayakan Potensi Pulau Lakkang Sebagai Daerah Tujuan Wisata di Kota Makassar - Nur Aisyah; Isfa Sastrawati; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
Lakkang Island is designated as a natural tourism area which has natural environmental conditions and has various potentials. However, the management and development of the potential of Lakkang Island to be used as a tourist area has not been maximized. This can be seen from the minimal tourist support facilities, the area is not well organized, and until now there has been no feasibility test for tourism potential so that the level of feasibility is not known which can be used as material for consideration for managers in developing Lakkang Island to the fullest. The purpose of this research is to inventory the potential of tourism objects and attractions and to assess the feasibility level of the potential of Lakkang Island as a tourist destination in Makassar City. This research is descriptive in nature by using spatial analysis and weighting analysis with the guidelines for Analysis of Operational Areas and Natural Tourism Attraction Objects (ADO-ODTWA) by the Directorate General of Forest Protection and Nature Conservation (PHKA) 2003. The results of this study indicate that Lakkang Island has a level value potential feasibility of 73.5% with the classification category 'High (A)', which means that this value indicates that Lakkang Island has the potential for attractiveness, accessibility, supporting facilities and infrastructure as well as the availability of supporting clean water, so it is feasible to be developed into one of the tourist destination in Makassar City.